The Impact of Video-Based Educational Interventions on Cervical Cancer, Pap Smear and HPV Vaccines - Drokow, Emmanuel Kwateng; Effah, Clement Yaw; Agboyibor, Clement; Sasu, Evans; Amponsem-Boateng, Cecilia; Akpabla, Gloria Selorm; Ahmed, Hafiz Abdul Waqas; Sun, Kai (Frontiers in Public Health, 2021)
Background: Video-based interventions have the potential to contribute to long-lasting improvements in health-seeking behaviours. Ghana's upsurge rate of information and communication technology usage presents an opportunity to improve the awareness of HPV vaccination and screening rates of cervical cancer among women in Ghana. This research aimed to assess the impact of video-based educational intervention centred on the Health Belief and Transtheoretical Models of behavioural changes in promoting HPV vaccination, cervical carcinoma awareness and willingness to have Pap smear test (PST) among women in Ghana. Methods: To achieve the intended sample size, convenient, purposive and stratified random sampling techniques were used. SPSS v. 23.0 was used in the data analysis. Percentages and frequencies were used to represent participants' demographic characteristics, knowledge of (1) cervical carcinoma, (2) human papillomavirus vaccine, and (3) Pap smear test. The chi-square test by McNemar was employed to evaluate variations in the post- and pre-intervention responses. A p-value < 0.05 was considered statistically significant. The level of significance was adjusted owing to multiple comparisons by using the Bonferroni's correction. Results: Before the intervention, 84.2% of the participant had some knowledge or information about cervical cancer, but after the intervention, 100% of the participant became aware of cervical cancer which represents 15.8% increment at a P < .001. The willingness to have a pap smear test increased from 35.8% to 94.2% (df=58.4%, P < .001) after the educational intervention. The willingness to be vaccinated increased from 47.5% to 81.7% (df=34.2%, P < .001) after the educational intervention. Six months after the intervention, participants were followed-up. 253 (42.2%) participants had gone for cervical cancer screening (Pap smear test) while 347 (57.8%) participants had not been screened. In terms of HPV vaccination, 192 participants (32.0%) had begun their HPV vaccination cycle. Conclusion: The study results show that health education, using leaflets, videos, discussions and lectures may be influential in perception changing, self-efficacy improvement and the understanding of cervical carcinoma screening and HPV vaccination.